Pengaruh Desain Penghawaan terhadap Kondisi Termal di Gereja Santo Petrus Sambiroto Semarang - Dewandaru, Ardian; Budi, Wahyu Setia; Hardiman, Gagoek (ARSITEKTURA, 2019)
Saint Peter Church Sambiroto located in the Semarang City which has tropical climate. The building has many openings like doors and bouvenlights. Currently in the east corridor are given tents to accommodate the number of congregations that exist, and on the east side the hallway is paired with banner to protect the east hallway from sun’s heat. The researcher will examine how openings play a role in creating thermal conditions in buildings. This research method uses field measurement techniques in the church regarding dry temperature, relative humidity and air movement in the church at each worship time in the morning and evening and at point where there are openings and not. After doing research, it was found that the temperature in the morning was still in a comfortable condition but at the evening temperature was above comfortable conditions. Even though all measuring points are affected by  fan, the point where has opening has low temperature than where has no opening, in the point where has banner have higher temperature than no banner. This proves that openings play a role in flowing air into the building and banners blocking the air to entering lobby and building area from the east side.